ANALISIS KOMITMEN ORGANISASI DALAM MELAKSANAKAN STANDAR OPERASIONAL PROSEDUR CONFINED SPACE ENTRY PADA TANGKI CRUDE OIL TERHADAP KESELAMATAN KERJA DI PERUSAHAAN X - Rhevi Dayana Sari; Bina Kurniawan; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Company X is a company engaged in the field of oil and gas. In the production process, there are some jobs that require workers entering the confined space. Work in confined space entry is work with high risk. Early in the year 2015 in the company there were X case accidents in confined space entry. One of the company's effort to minimize the number of accidents in the X on the confined space entry work is by implementing standard operational procedures. To achieve the optimal implementation of the SOP in the workplace, Organizational Commitment of the company X, that is a commitment from management and the commitment of all employees is needed. The purpose of this study was to describe the form of organizational commitment in company X in carrying out standards operational procedures (SOP) of confined space entry on crude oil tanks. This study uses qualitative methods by conducting in-depth interviews and observations. The subject of this research consists of four main informants and two informants triangulation. The results of this research show that the company X had done the dimensions of organizational commitment in implementing the SOP confined space entry either from affective commitment, continuance commitment and normative commitment. However, on the dimensions of the affective commitment in terms of the increased safety and occupational health program is needed, with a means of involving all employees in the coordination meeting, provide training about confined space entry to workers who have yet to get the training and the provision of the amount of protective tools that correspond to the number of employees in field. On dimension of continuance commitment that reviewed the system of punishment needs to be on the increase in the implementation approaches, to workers who do not use protective tools themselves should be given verbally and are not allowed to work until the worker using a complete personal protective equipment in accordance with SOP.